2022
DOI: 10.3389/fonc.2022.863609
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcomes and Pattern of Relapse After SABR for Oligometastatic Prostate Cancer

Abstract: IntroductionThe addition of stereotactic ablative radiotherapy (SABR) to standard of care for patients with oligometastatic prostate cancer has the potential of improving survival and delaying further metastases. The primary aim of this analysis is to report survival outcomes and pattern of recurrence of patients with hormone-sensitive (HSPC) and castrate-resistant (CRPC) oligometastatic prostate cancer treated with SABR.MethodsThis is a single-center retrospective study of patients with oligometastatic prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Mercier et al reported on the association between MDT and short-term ADT, observing improved outcomes. They found that combining MDT with short-term ADT ( n = 18) led to enhanced biochemical PFS compared to MDT alone ( n = 30) [ 22 ]. In contrast, Pastorello et al studied 95 patients with 150 nonspinal bone metastases diagnosed via PSMA-PET.…”
Section: Retrospective Seriesmentioning
confidence: 99%
“…Mercier et al reported on the association between MDT and short-term ADT, observing improved outcomes. They found that combining MDT with short-term ADT ( n = 18) led to enhanced biochemical PFS compared to MDT alone ( n = 30) [ 22 ]. In contrast, Pastorello et al studied 95 patients with 150 nonspinal bone metastases diagnosed via PSMA-PET.…”
Section: Retrospective Seriesmentioning
confidence: 99%